Productivity increase through the application of Lean, TQM and SLP TOOLS in the peruvian craft brewery cluster - Ulloa Durand, Jose Alonso (2023)
The brewing industry has evolved over the years, attracting many customers. Therefore, due to the diversity of tastes and preferences, craft brewing companies were born, becoming the livelihood of thousands of families in the national territory. However, most of them are empirical or do not have a correct working method, which adds a lot of time and a complicated production process. In addition, there is a lack of efficient plant design and they do not consider order, cleanliness, and organization in their operations due to the precariousness of knowledge of improvement tools. Therefore, the main objective of this investigation is to increase productivity in the areas of supply and production through the development of an integrated model of 5S, Standardized Work, Systematic Layout Planning (SLP) and Total Quality Management (TQM) framework. Through the implementation of this Lean model and its corresponding simulation in Arena software, it was possible to increase productivity by 15.21%, increasing production and reducing times, in addition to increasing revenues by approximately PEN 24,000.